MEGAFAST SUPERBIKES - Farndon, John; Edwards, Mat; Pyke, Jeremy (Edenbridge Kent, Great Britian : Hungry Tomato, 2015)
Superbikes Test ride the Lotus C-O1, the electric Lightning LS218, the Kawasaki H2R Ninja and more, to reach speeds up to 218 mph. Find out about racers, race tracks and engines.
"ROAR AWAY ON TURBOCHARGED STORMERS" - coverpage
Includes index.
Keywords: Superbikes -- Juvenile literature; Motorcycles